2011
DOI: 10.1007/s11803-011-0053-5
|View full text |Cite
|
Sign up to set email alerts
|

Site specific probabilistic seismic hazard analysis at Dubai Creek on the west coast of UAE

Abstract: A probabilistic seismic hazard analysis (PSHA) was conducted to establish the hazard spectra for a site located at Dubai Creek on the west coast of the United Arab Emirates (UAE). The PSHA considered all the seismogenic sources that affect the site, including plate boundaries such as the Makran subduction zone, the Zagros fold-thrust region and the transition fault system between them; and local crustal faults in UAE. PSHA indicated that local faults dominate the hazard. The peak ground acceleration (PGA) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Zhu et al ., ; Bommer and Acevedo, ). The site of the reference structures (Dubai, UAE) is vulnerable to earthquakes originated from different seismic sources, namely long‐distance events along with earthquakes from local seismic faults (Mwafy et al ., ; Aldama‐Bustos et al ., ; Shama, ; Khan et al ., ). There is a characteristic difference in earthquake‐induced response from the above‐mentioned two scenarios.…”
Section: Earthquake Ground Motions and Performance Indicatorsmentioning
confidence: 99%
“…Zhu et al ., ; Bommer and Acevedo, ). The site of the reference structures (Dubai, UAE) is vulnerable to earthquakes originated from different seismic sources, namely long‐distance events along with earthquakes from local seismic faults (Mwafy et al ., ; Aldama‐Bustos et al ., ; Shama, ; Khan et al ., ). There is a characteristic difference in earthquake‐induced response from the above‐mentioned two scenarios.…”
Section: Earthquake Ground Motions and Performance Indicatorsmentioning
confidence: 99%
“…The site of the reference steel buildings (Dubai, UAE) is characterized by longdistance events generated from Southern Iran and the earthquakes from the local seismic faults (Aldama-Bustos et al, 2009;Mwafy et al, 2006;Shama, 2011). The present study focuses on severe distant earthquake scenarios based on the conclusions drawn from recent fragility assessment studies carried out on multi-story buildings with varying heights, which indicated a higher impact on the response of the buildings with long-distance events (Mwafy et al, 2006).…”
Section: Earthquake Ground Motions Uncertaintymentioning
confidence: 99%
“…This area was previously considered a non-seismic region [28]. However, based on several recent seismic hazard studies, the UAE is currently regarded as a low-to-medium seismicity region [29][30][31][32][33]. It is also noteworthy that the design approach and criteria were updated in other regions, such as the U.S., after major earthquakes (e.g., Loma Prieta in 1989, [8]).…”
Section: Introductionmentioning
confidence: 99%